GONAD REMATURATION ON Pangasionodon hypophthalmus FEMALE THROUGH INJECTION OF PREGNANT MARE SERUM GONADOTROPIN AND HUMAN CHORIONIC GONADOTROPIN - Evi Tahapari; Jadmiko Darmawan; Raden Roro Sri Pudji Sinarni Dewi; Wahyu Pamungkas; Huria Marnis (Center for Fisheries Research, Agency for Marine and Fisheries Research and Human Resource, 2014)
The success of spawning is influenced by internal and external factors. One of the factors that affect the var iabi li ty of Pangasianodon hypophthalmus female reproductive is the change of seasons that cause disrupted continuity of the seed availability, especially in the dry season. In the present study, combination of PMSG (pregnant mare serum gonadotropin) + HCG (hormone chorionic gonadotropin) hormone injections was done to induce gonad development. The treatments in this study were without hormone injections as control (A), injection of PMSG 10 IU/kg + HCG 10 IU/kg (B), and injection of PMSG 20 IU/kg HCG + 10 IU/kg (C). Injections were conducted at intervals of two weeks as many as six times. The results showed that gonad maturation generally occurs 2-4 weeks after estradiol-17 peak. PMSG + HCG hormone injections gave a significant effect on increasing the quantity and quality of eggs production. The fecundity in the A, B, C treatments, were 233,700±220,676; 300,305±24,581 and 488,433±142,228; respectively. Number of larvae produced from the A, B, C treatments, were 156,979±170,838; 229,997±18,081 and 362,713±101,850; respectively. Combination of PMSG 20 IU/kg + HCG 10 IU/kg hormone injection gave the best result on fecundity and the number of larvae production.